Credit Where Credit is Due?: Race, Gender, and Discrimination in the Credit Scores of Business Startups. Issue 4 (2015) - Henderson, Loren; Herring, Cedric; Horton, Hayward Derrick; Thomas, Melvin
This research seeks to understand the degree to which credit scores of new business startups are influenced by racial or gender discrimination. It examines the degree to which access to business credit lines is influenced by racial and gender-related factors that go beyond would-be borrowers' credit scores. Using credit data from new startups, the analysis finds that, when controlling for firm and human capital characteristics, Black-owned startups receive lower than expected business credit scores. Whites are more favorably treated in credit score determination than are African Americans with the same firm characteristics and owner characteristics. Moreover, Whites are more favorably treated when it comes to access to credit lines than are African Americans, Latinos, and Asians with the same firm characteristics, owner characteristics, and credit scores. Men are more favorably treated when it comes to access to credit lines than are women. A Blinder-Oaxaca decomposition suggests that credit lines for Black-owned businesses would more than double, Latino-owned businesses' lines of credit would nearly triple, Asian-owned businesses' lines of credit would more than triple, and those where the primary owners are women would be more than twice as large if their business lines of credit were determined in the same way as those for businesses owned primarily by Whites and by men. The implications of these results are discussed.